High-permeability composite non-woven fabric and processing technology thereof

By designing a composite structure of hydrophilic, antibacterial and hydrophobic layers in nonwoven fabrics, the problem of insufficient permeability of traditional nonwoven fabric materials is solved, and the high permeability and antibacterial performance is improved, which is suitable for applications in multiple fields.

CN119795709AActive Publication Date: 2025-04-11JIANGSU HUALONG NON WOVEN

Patent Information

Application Number
CN202510026591.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-11
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

Due to insufficient hydrophilicity and permeability of traditional non-woven materials, they have limited their application in medical, sanitary and environmental protection fields, and the market demand for high-performance non-woven fabrics is growing.

Method used

By designing the structure of the composite nonwoven fabric, the hydrophilic nonwoven fabric layer is coated with cast film liquid, and acrylic fibers and silver fibers are blended into an antibacterial mesh layer, and polypropylene melt-extruded into a hydrophobic nonwoven fabric layer, and high permeability composite nonwoven fabric is obtained by stacking and needle-punching curing.

Benefits of technology

It significantly improves the permeability and antibacterial properties of the materials, while improving the mechanical properties, and is suitable for medical, health and environmental protection fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-permeability composite non-woven fabric and a processing technology thereof, and relates to the technical field of non-woven fabric processing. Comprising the following steps: step 1, coating the surface of a non-woven fabric primary product with a membrane casting solution to obtain a hydrophilic non-woven fabric layer; blending acrylic fibers and silver fibers in a mass ratio of (50-60): 1 to obtain an antibacterial grid layer; carrying out melt extrusion on polypropylene, and then carrying out compression shaping to obtain a hydrophobic non-woven fabric layer; 2, sequentially stacking the hydrophilic non-woven fabric layer, the antibacterial grid layer and the hydrophobic non-woven fabric layer from top to bottom, and performing needling curing to obtain the high-permeability composite non-woven fabric. The composite non-woven fabric has the beneficial effects that the structure of the composite non-woven fabric is designed, so that the hydrophilic performance of the hydrophilic non-woven fabric layer is improved, and the overall permeability of the material is effectively improved; meanwhile, the nano titanium oxide is modified, so that the antibacterial effect and the mechanical property of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of non-woven fabric processing, in particular to a high-permeability composite non-woven fabric and a processing technology thereof. Background Art

[0002] In modern society, nonwoven fabrics, as a new type of textile material, have attracted widespread attention due to their excellent physical properties, high efficiency of the production process, and cost-effectiveness. The application range of nonwoven fabrics is very wide, ranging from agricultural covering materials, sanitary products, industrial fabrics to disposable surgical gowns in the medical field. However, traditional nonwoven fabrics are usually made of synthetic polymers such as polypropylene, polyester, etc. Although these materials provide good performance, they often have poor hydrophilicity and permeability, which limits their use in certain specific applications. Moreover, with the advancement of science and technology and the improvement of environmental awareness, the market demand for high-performance nonwoven fabrics is growing, especially those with high permeability, excellent liquid transmission capabilities and good biocompatibility. These characteristics are crucial to improving the application effect of nonwoven fabrics in the fields of medicine, hygiene and environmental protection. Therefore, it is of great significance to prepare a high permeability composite nonwoven fabric. Summary of the invention

[0003] The purpose of the present invention is to provide a high-permeability composite nonwoven fabric and a processing technology thereof to solve the problems raised in the prior art.

[0004] To achieve the above object, the present invention provides the following technical solutions: A processing technology for a high-permeability composite nonwoven fabric comprises the following steps: Step 1: coating the casting liquid on the surface of the non-woven fabric to obtain a hydrophilic non-woven fabric layer; blending acrylic fiber and silver fiber in a mass ratio of (50-60) : 1 to obtain an antibacterial mesh layer; and melt-extruding polypropylene and compressing and shaping to obtain a hydrophobic non-woven fabric layer; Step 2: stack the hydrophilic non-woven fabric layer, the antibacterial mesh layer, and the hydrophobic non-woven fabric layer from top to bottom, and solidify them by needle punching to obtain a high-permeability composite non-woven fabric.

[0005] More optimally: the preparation process of the hydrophilic non-woven fabric layer is: S1: Carding polyamide fiber and polyester fiber into a web, hot air bonding, hot rolling, cooling and forming, to obtain nonwoven fabric A; S2: treating the non-woven fabric A with plasma to obtain a primary non-woven fabric; S3: The casting solution is evenly coated on the surface of the non-woven fabric, and then immersed in an ethanol solution for 30-40 minutes and dried to obtain a hydrophilic non-woven fabric layer.

[0006] More optimally, the casting solution comprises the following components: by weight, 5-8 parts of poly-L-lysine, 3-5 parts of glutaraldehyde, 10-12 parts of polyvinyl alcohol, 4-5 parts of acetic acid, and 1-2 parts of modified nano-titanium oxide.

[0007] More optimally: the preparation process of the modified nano titanium oxide is: (1) Add nano titanium oxide and γ-aminopropyltriethoxysilane to a 10-20wt% ethanol aqueous solution in sequence, heat to 70-80°C, stir for 4-5h, wash, and dry to obtain amino nano titanium oxide; (2) Mix the amino-modified nano-titanium oxide, 2-2 (bromoacetyl) benzoic acid and dimethyl sulfoxide, stir for 30-40 minutes, then add dicyclohexylcarbodiimide and N-hydroxysuccinimide, continue stirring for 10-12 minutes, heat to 40-50°C, react for 5-8 hours, and obtain an intermediate; (3) The intermediate, tetrahydrofuran and triethylamine are mixed and stirred for 30-40 minutes. Under a protective atmosphere, N-butyl-m-toluidine is added dropwise. The temperature is raised to 60-70°C, and the reaction is carried out for 3-4 hours. The mixture is cooled to room temperature, washed and dried to obtain modified nano-titanium oxide.

[0008] More optimally, the amino-type nano-titanium oxide comprises the following components: by weight, 20-25 parts of nano-titanium oxide, 100-150 parts of ethanol aqueous solution, and 8-10 parts of γ-aminopropyltriethoxysilane; the intermediate comprises the following components: by weight, 30-35 parts of amino-type nano-titanium oxide, 10-12 parts of 2-2 (bromoacetyl) benzoic acid, 200-250 parts of dimethyl sulfoxide, 0.5-0.7 parts of dicyclohexylcarbodiimide, and 0.8-1 parts of N-hydroxysuccinimide; the modified nano-titanium oxide comprises the following components: by weight, 10-15 parts of intermediate, 80-100 parts of tetrahydrofuran, 3-4 parts of triethylamine, and 6-8 parts of N-butyl-m-toluidine.

[0009] More optimally: in the non-woven fabric A, the mass ratio of polyamide fiber to polyester fiber is (2-3):1; the temperature of the hot rolling process is 100-120°C; and the temperature of the cooling molding is 15-20°C.

[0010] More optimally, the parameters of plasma treatment are: power 50-60 W, time 3-9 min, oxygen flux 50-80 mL / min.

[0011] More optimally: the preparation process of the hydrophobic non-woven fabric layer is: polypropylene and modified nano titanium oxide are melt-extruded at 220-230°C, and after cooling, they are compressed and shaped at a temperature of 150-160°C and a pressure of 4-5Kg to obtain a hydrophobic non-woven fabric layer.

[0012] More optimally, the hydrophobic nonwoven fabric layer comprises the following components: 100-120 parts by weight of polypropylene and 5-6 parts of modified nano titanium oxide.

[0013] The present invention improves the hydrophilicity of the hydrophilic nonwoven layer by designing the structure of the composite nonwoven fabric, thereby effectively improving the overall permeability of the material; at the same time, the nano-titanium oxide is modified to improve the antibacterial effect and mechanical properties of the material. The details are as follows: First, the hydrophilic non-woven fabric layer is obtained by coating the casting solution on the surface of the non-woven fabric primary product, wherein the poly-L-lysine in the casting solution contains a large number of amino groups and amide groups, which can form hydrogen bonds with water molecules, thereby improving the hydrophilicity and permeability of the material; at the same time, the amino groups in its molecules can be protonated in the solution to form cations, thereby improving the antibacterial properties of the material, and in the presence of glutaraldehyde, covalent bonds are formed through Schiff base reaction, thereby improving the washing durability of the coating; Second, nano titanium oxide is added to the casting solution and the hydrophobic non-woven fabric layer. Since nano titanium oxide is prone to aggregation in the solution, the present invention performs quaternary ammonium modification on its surface and introduces a longer molecular chain, which effectively improves its dispersibility in the solution; at the same time, the quaternary ammonium groups on the surface also effectively improve the overall antibacterial performance. In addition, nano titanium oxide is used as a reinforcing material, and the mechanical properties of the composite non-woven fabric are also improved. DETAILED DESCRIPTION

[0014] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.

[0015] It should be noted that the following parts are by weight, and the purchase manufacturers of all raw materials involved in the present invention are exemplified without any special restrictions: in the following embodiments, 2-2 (bromoacetyl) benzoic acid CAS is 7399-67-9, and the purchase manufacturer is Shanghai Huayuan Century Trading Co., Ltd.; N-butyl-m-toluidine CAS is 60995-75-7; poly-L-lysine product number is 60716ES08.

[0016] Embodiment 1: A processing technology for a high-permeability composite nonwoven fabric comprises the following steps: Step 1: The preparation process of the hydrophilic non-woven fabric layer is: S1: Carding polyamide fiber and polyester fiber into a web, hot air bonding, then hot rolling at 100°C, and cooling at 15°C to obtain nonwoven fabric A; S2: The non-woven fabric A is subjected to plasma treatment, and the plasma parameters are: power 50 W, time 3 min, oxygen flux 50 mL / min, to obtain a primary non-woven fabric; S3: The casting solution is evenly coated on the surface of the non-woven fabric, and then immersed in an ethanol solution for 30 minutes and dried to obtain a hydrophilic non-woven fabric layer. The casting solution includes the following components: by weight, 5 parts of poly-L-lysine, 3 parts of glutaraldehyde, 10 parts of polyvinyl alcohol, 4 parts of acetic acid, and 1 part of modified nano titanium oxide. The preparation process of the modified nano titanium oxide is: (1) 20 parts of nano titanium oxide, 100 parts of 10 wt% ethanol aqueous solution, and 8 parts of γ-aminopropyltriethoxysilane were mixed, heated to 70° C., stirred for 4 h, washed, and dried to obtain amino nano titanium oxide; (2) 30 parts of amino-modified nano-titanium oxide, 10 parts of 2-2 (bromoacetyl) benzoic acid, and 200 parts of dimethyl sulfoxide were mixed and stirred for 30 minutes, and then 0.5 parts of dicyclohexylcarbodiimide and 0.8 parts of N-hydroxysuccinimide were added, and the mixture was stirred for 10 minutes. The mixture was heated to 40°C and reacted for 5 hours to obtain an intermediate. (3) 10 parts of the intermediate, 80 parts of tetrahydrofuran and 3 parts of triethylamine were mixed and stirred for 30 minutes. Under nitrogen, 6 parts of N-butyl-m-toluidine were added dropwise. The temperature was raised to 60°C and the reaction was carried out for 3 hours. The mixture was cooled to room temperature, washed and dried to obtain modified nano-titanium oxide.

[0017] Preparation of the antibacterial mesh layer: acrylic fiber and silver fiber are blended in a mass ratio of 50:1 to obtain the antibacterial mesh layer.

[0018] The preparation process of the hydrophobic non-woven fabric layer is as follows: polypropylene and modified nano titanium oxide are melt-extruded at 220° C., and after cooling, they are compressed and shaped at a temperature of 150° C. and a pressure of 4 Kg to obtain the hydrophobic non-woven fabric.

[0019] Step 2: stack the hydrophilic non-woven fabric layer, the antibacterial mesh layer, and the hydrophobic non-woven fabric layer from top to bottom, and solidify them by needle punching to obtain a high-permeability composite non-woven fabric.

[0020] Embodiment 2: A processing technology for a high-permeability composite nonwoven fabric comprises the following steps: Step 1: The preparation process of the hydrophilic non-woven fabric layer is: S1: Carding polyamide fiber and polyester fiber into a web, hot-air bonding, and then hot-rolling at 120°C and cooling at 20°C to obtain nonwoven fabric A; S2: The non-woven fabric A is subjected to plasma treatment, and the plasma parameters are: power 60 W, time 9 min, oxygen flux 80 mL / min, to obtain a primary non-woven fabric; S3: The casting solution is evenly coated on the surface of the non-woven fabric, and then immersed in an ethanol solution for 40 minutes and dried to obtain a hydrophilic non-woven fabric layer. The casting solution includes the following components: by weight, 8 parts of poly-L-lysine, 5 parts of glutaraldehyde, 12 parts of polyvinyl alcohol, 5 parts of acetic acid, and 2 parts of modified nano titanium oxide. The preparation process of the modified nano titanium oxide is: (1) 25 parts of nano titanium oxide, 150 parts of 20 wt% ethanol aqueous solution, and 10 parts of γ-aminopropyltriethoxysilane were mixed, heated to 80° C., stirred for 5 h, washed, and dried to obtain amino nano titanium oxide; (2) 35 parts of amino-modified nano-titanium oxide, 12 parts of 2-2 (bromoacetyl) benzoic acid, and 250 parts of dimethyl sulfoxide were mixed and stirred for 40 minutes, and then 0.7 parts of dicyclohexylcarbodiimide and 1 part of N-hydroxysuccinimide were added, and the mixture was stirred for 12 minutes. The temperature was raised to 50°C and the reaction was carried out for 8 hours to obtain an intermediate; (3) 15 parts of the intermediate, 100 parts of tetrahydrofuran and 4 parts of triethylamine were mixed and stirred for 40 minutes. Under nitrogen, 8 parts of N-butyl-m-toluidine were added dropwise. The temperature was raised to 70°C and the reaction was carried out for 4 hours. The mixture was cooled to room temperature, washed and dried to obtain modified nano-titanium oxide.

[0021] The preparation process of the antibacterial mesh layer is as follows: acrylic fiber and silver fiber are blended in a mass ratio of 50:1 to obtain the antibacterial mesh layer.

[0022] The preparation process of the hydrophobic non-woven fabric layer is as follows: polypropylene and modified nano titanium oxide are melt-extruded at 230° C., and after cooling, they are compressed and shaped at a temperature of 160° C. and a pressure of 5 Kg to obtain the hydrophobic non-woven fabric layer.

[0023] Step 2: stack the hydrophilic non-woven fabric layer, the antibacterial mesh layer, and the hydrophobic non-woven fabric layer from top to bottom, and solidify them by needle punching to obtain a high-permeability composite non-woven fabric.

[0024] Embodiment 3: A processing technology for a high-permeability composite nonwoven fabric comprises the following steps: Step 1: The preparation process of the hydrophilic non-woven fabric layer is: S1: Carding polyamide fiber and polyester fiber into a web, hot-air bonding, and then hot-rolling at 110°C and cooling at 18°C ​​to obtain nonwoven fabric A; S2: The non-woven fabric A is subjected to plasma treatment, and the plasma parameters are: power 55 W, time 5 min, oxygen flux 60 mL / min, to obtain a primary non-woven fabric; S3: The casting solution is evenly coated on the surface of the non-woven fabric, and then immersed in an ethanol solution for 35 minutes and dried to obtain a hydrophilic non-woven fabric layer. The casting solution includes the following components: by weight, 6 parts of poly-L-lysine, 4 parts of glutaraldehyde, 11 parts of polyvinyl alcohol, 4.5 parts of acetic acid, and 1.5 parts of modified nano titanium oxide. The preparation process of the modified nano titanium oxide is: (1) 22 parts of nano titanium oxide, 120 parts of 15 wt% ethanol aqueous solution, and 9 parts of γ-aminopropyltriethoxysilane were mixed, heated to 75° C., stirred for 4.5 h, washed, and dried to obtain amino nano titanium oxide; (2) 32 parts of amino-modified nano-titanium oxide, 11 parts of 2-2 (bromoacetyl) benzoic acid, and 220 parts of dimethyl sulfoxide were mixed and stirred for 35 minutes, and then 0.6 parts of dicyclohexylcarbodiimide and 0.9 parts of N-hydroxysuccinimide were added, and the mixture was stirred for 11 minutes. The temperature was raised to 45°C and the reaction was carried out for 6 hours to obtain an intermediate; (3) 12 parts of the intermediate, 90 parts of tetrahydrofuran and 3.5 parts of triethylamine were mixed and stirred for 35 minutes. Under nitrogen, 7 parts of N-butyl-m-toluidine were added dropwise. The temperature was raised to 65°C and the reaction was carried out for 3.5 hours. The mixture was cooled to room temperature, washed and dried to obtain modified nano-titanium oxide.

[0025] The preparation process of the antibacterial mesh layer is as follows: acrylic fiber and silver fiber are blended in a mass ratio of 50:1 to obtain the antibacterial mesh layer.

[0026] The preparation process of the hydrophobic non-woven fabric layer is as follows: polypropylene and modified nano titanium oxide are melt-extruded at 225° C., and after cooling, they are compressed and shaped at a temperature of 155° C. and a pressure of 4.5 Kg to obtain the hydrophobic non-woven fabric layer.

[0027] Step 2: stack the hydrophilic non-woven fabric layer, the antibacterial mesh layer, and the hydrophobic non-woven fabric layer from top to bottom, and solidify them by needle punching to obtain a high-permeability composite non-woven fabric.

[0028] Comparative Example 1: No modified nano titanium oxide was added during the preparation of the composite non-woven fabric, and the rest was the same as in Example 3, as follows: Step 1: The preparation process of the hydrophilic non-woven fabric layer is: S1: Carding polyamide fiber and polyester fiber into a web, hot-air bonding, and then hot-rolling at 110°C and cooling at 18°C ​​to obtain nonwoven fabric A; S2: The non-woven fabric A is subjected to plasma treatment, and the plasma parameters are: power 55 W, time 5 min, oxygen flux 60 mL / min, to obtain a primary non-woven fabric; S3: The casting solution is evenly coated on the surface of the non-woven fabric, and then immersed in an ethanol solution for 35 minutes and dried to obtain a hydrophilic non-woven fabric layer. The casting solution includes the following components: by weight, 6 parts of poly-L-lysine, 4 parts of glutaraldehyde, 11 parts of polyvinyl alcohol, and 4.5 parts of acetic acid.

[0029] The preparation process of the antibacterial mesh layer is as follows: acrylic fiber and silver fiber are blended in a mass ratio of 50:1 to obtain the antibacterial mesh layer.

[0030] The preparation process of the hydrophobic non-woven fabric layer is as follows: polypropylene is melt-extruded at 200° C., and after cooling, it is compressed and shaped at a temperature of 155° C. and a pressure of 4.5 Kg to obtain the hydrophobic non-woven fabric layer.

[0031] Step 2: stack the hydrophilic non-woven fabric layer, the antibacterial mesh layer, and the hydrophobic non-woven fabric layer from top to bottom, and solidify them by needle punching to obtain a high-permeability composite non-woven fabric.

[0032] Comparative Example 2: Poly-L-lysine was not added to the casting solution, and the rest was the same as in Example 3, specifically as follows: Step 1: The preparation process of the hydrophilic non-woven fabric layer is: S1: Carding polyamide fiber and polyester fiber into a web, hot-air bonding, and then hot-rolling at 110°C and cooling at 18°C ​​to obtain nonwoven fabric A; S2: The non-woven fabric A is subjected to plasma treatment, and the plasma parameters are: power 55 W, time 5 min, oxygen flux 60 mL / min, to obtain a primary non-woven fabric; S3: The casting solution is evenly coated on the surface of the non-woven fabric, and then immersed in an ethanol solution for 35 minutes and dried to obtain a hydrophilic non-woven fabric layer. The casting solution includes the following components: 4 parts of glutaraldehyde, 11 parts of polyvinyl alcohol, 4.5 parts of acetic acid, and 1.5 parts of modified nano titanium oxide. The preparation process of the modified nano titanium oxide is: (1) 22 parts of nano titanium oxide, 120 parts of 15 wt% ethanol aqueous solution, and 9 parts of γ-aminopropyltriethoxysilane were mixed, heated to 75° C., stirred for 4.5 h, washed, and dried to obtain amino nano titanium oxide; (2) 32 parts of amino-modified nano-titanium oxide, 11 parts of 2-2 (bromoacetyl) benzoic acid, and 220 parts of dimethyl sulfoxide were mixed and stirred for 35 minutes, and then 0.6 parts of dicyclohexylcarbodiimide and 0.9 parts of N-hydroxysuccinimide were added, and the mixture was stirred for 11 minutes. The temperature was raised to 45°C and the reaction was carried out for 6 hours to obtain an intermediate; (3) 12 parts of the intermediate, 90 parts of tetrahydrofuran and 3.5 parts of triethylamine were mixed and stirred for 35 minutes. Under nitrogen, 7 parts of N-butyl-m-toluidine were added dropwise. The temperature was raised to 65°C and the reaction was carried out for 3.5 hours. The mixture was cooled to room temperature, washed and dried to obtain modified nano-titanium oxide.

[0033] The preparation process of the antibacterial mesh layer is as follows: acrylic fiber and silver fiber are blended in a mass ratio of 50:1 to obtain the antibacterial mesh layer.

[0034] The preparation process of the hydrophobic non-woven fabric layer is as follows: polypropylene and modified nano titanium oxide are melt-extruded at 225° C., and after cooling, they are compressed and shaped at a temperature of 155° C. and a pressure of 4.5 Kg to obtain the hydrophobic non-woven fabric layer.

[0035] Step 2: stack the hydrophilic non-woven fabric layer, the antibacterial mesh layer, and the hydrophobic non-woven fabric layer from top to bottom, and solidify them by needle punching to obtain a high-permeability composite non-woven fabric.

[0036] Comparative Example 3: No polyvinyl alcohol and acetic acid were added to the casting solution, and the rest was the same as in Example 3, specifically as follows: Step 1: The preparation process of the hydrophilic non-woven fabric layer is: S1: Carding polyamide fiber and polyester fiber into a web, hot-air bonding, and then hot-rolling at 110°C and cooling at 18°C ​​to obtain nonwoven fabric A; S2: The non-woven fabric A is subjected to plasma treatment, and the plasma parameters are: power 55 W, time 5 min, oxygen flux 60 mL / min, to obtain a primary non-woven fabric; S3: The casting solution is evenly coated on the surface of the non-woven fabric, and then immersed in an ethanol solution for 35 minutes and dried to obtain a hydrophilic non-woven fabric layer. The casting solution includes the following components: 6 parts of poly-L-lysine, 4 parts of glutaraldehyde, and 1.5 parts of modified nano titanium oxide by weight. The preparation process of the modified nano titanium oxide is: (1) 22 parts of nano titanium oxide, 120 parts of 15 wt% ethanol aqueous solution, and 9 parts of γ-aminopropyltriethoxysilane were mixed, heated to 75° C., stirred for 4.5 h, washed, and dried to obtain amino nano titanium oxide; (2) 32 parts of amino-modified nano-titanium oxide, 11 parts of 2-2 (bromoacetyl) benzoic acid, and 220 parts of dimethyl sulfoxide were mixed and stirred for 35 minutes, and then 0.6 parts of dicyclohexylcarbodiimide and 0.9 parts of N-hydroxysuccinimide were added, and the mixture was stirred for 11 minutes. The temperature was raised to 45°C and the reaction was carried out for 6 hours to obtain an intermediate; (3) 12 parts of the intermediate, 90 parts of tetrahydrofuran and 3.5 parts of triethylamine were mixed and stirred for 35 minutes. Under nitrogen, 7 parts of N-butyl-m-toluidine were added dropwise. The temperature was raised to 65°C and the reaction was carried out for 3.5 hours. The mixture was cooled to room temperature, washed and dried to obtain modified nano-titanium oxide.

[0037] The preparation process of the antibacterial mesh layer is as follows: acrylic fiber and silver fiber are blended in a mass ratio of 50:1 to obtain the antibacterial mesh layer.

[0038] The preparation process of the hydrophobic non-woven fabric layer is as follows: polypropylene and modified nano titanium oxide are melt-extruded at 225° C., and after cooling, they are compressed and shaped at a temperature of 155° C. and a pressure of 4.5 Kg to obtain the hydrophobic non-woven fabric layer.

[0039] Step 2: stack the hydrophilic non-woven fabric layer, the antibacterial mesh layer, and the hydrophobic non-woven fabric layer from top to bottom, and solidify them by needle punching to obtain a high-permeability composite non-woven fabric.

[0040] Comparative Example 4: During the preparation of the hydrophilic non-woven fabric layer, no plasma treatment was performed, and the rest was the same as in Example 3, as follows: Step 1: The preparation process of the hydrophilic non-woven fabric layer is: S1: Carding polyamide fiber and polyester fiber into a web, hot-air bonding, and then hot-rolling at 110°C and cooling at 18°C ​​to obtain a non-woven fabric. S2: The casting solution is evenly coated on the surface of the non-woven fabric, and then immersed in an ethanol solution for 35 minutes and dried to obtain a hydrophilic non-woven fabric layer. The casting solution includes the following components: by weight, 6 parts of poly-L-lysine, 4 parts of glutaraldehyde, 11 parts of polyvinyl alcohol, 4.5 parts of acetic acid, and 1.5 parts of modified nano titanium oxide. The preparation process of the modified nano titanium oxide is: (1) 22 parts of nano titanium oxide, 120 parts of 15 wt% ethanol aqueous solution, and 9 parts of γ-aminopropyltriethoxysilane were mixed, heated to 75° C., stirred for 4.5 h, washed, and dried to obtain amino nano titanium oxide; (2) 32 parts of amino-modified nano-titanium oxide, 11 parts of 2-2 (bromoacetyl) benzoic acid, and 220 parts of dimethyl sulfoxide were mixed and stirred for 35 minutes, and then 0.6 parts of dicyclohexylcarbodiimide and 0.9 parts of N-hydroxysuccinimide were added, and the mixture was stirred for 11 minutes. The temperature was raised to 45°C and the reaction was carried out for 6 hours to obtain an intermediate; (3) 12 parts of the intermediate, 90 parts of tetrahydrofuran and 3.5 parts of triethylamine were mixed and stirred for 35 minutes. Under nitrogen, 7 parts of N-butyl-m-toluidine were added dropwise. The temperature was raised to 65°C and the reaction was carried out for 3.5 hours. The mixture was cooled to room temperature, washed and dried to obtain modified nano-titanium oxide.

[0041] The preparation process of the antibacterial mesh layer is as follows: acrylic fiber and silver fiber are blended in a mass ratio of 50:1 to obtain the antibacterial mesh layer.

[0042] The preparation process of the hydrophobic non-woven fabric layer is as follows: polypropylene and modified nano titanium oxide are melt-extruded at 225° C., and after cooling, they are compressed and shaped at a temperature of 155° C. and a pressure of 4.5 Kg to obtain the hydrophobic non-woven fabric layer.

[0043] Step 2: stack the hydrophilic non-woven fabric layer, the antibacterial mesh layer, and the hydrophobic non-woven fabric layer from top to bottom, and solidify them by needle punching to obtain a high-permeability composite non-woven fabric.

[0044] Performance test: The composite nonwoven fabrics obtained in Examples 1-3 and Comparative Examples 1-4 were subjected to water penetration test by electrical measurement, tensile performance test, and antibacterial rate test according to GB-T / 20944.3 standard. The results are shown in the table:

[0045] Table 1 Conclusion: Examples 1-3 improve the hydrophilicity of the hydrophilic nonwoven layer by designing the structure of the composite nonwoven fabric, thereby effectively improving the overall permeability of the material; at the same time, the nano-titanium oxide is modified to improve the antibacterial effect and mechanical properties of the material. In Comparative Example 1, modified nano-titanium oxide is not added during the preparation of the composite nonwoven fabric, which reduces the antibacterial and mechanical properties of the material; in Comparative Example 2, poly-L-lysine is not added to the casting liquid, which reduces the permeability and antibacterial properties of the composite nonwoven fabric; in Comparative Example 3, polyvinyl alcohol and acetic acid are not added to the casting liquid, which reduces the hydrophilic effect of the hydrophilic nonwoven layer, thereby reducing the overall permeability of the material; in Comparative Example 4, plasma treatment is not performed during the preparation of the hydrophilic nonwoven layer, and the coating effect of the casting liquid is reduced, thereby reducing the hydrophilic effect of the hydrophilic nonwoven layer and reducing the performance.

[0046] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A processing technology for a high-permeability composite nonwoven fabric, characterized in that: The following steps are involved: Step 1: coating the casting liquid on the surface of the non-woven fabric to obtain a hydrophilic non-woven fabric layer; blending acrylic fiber and silver fiber in a mass ratio of (50-60) : 1 to obtain an antibacterial mesh layer; and melt-extruding polypropylene and compressing and shaping to obtain a hydrophobic non-woven fabric layer; Step 2: stack the hydrophilic non-woven fabric layer, the antibacterial mesh layer, and the hydrophobic non-woven fabric layer from top to bottom, and solidify them by needle punching to obtain a high-permeability composite non-woven fabric.

2. The processing technology of a high permeability composite nonwoven fabric according to claim 1, characterized in that: The preparation process of the hydrophilic non-woven fabric layer is as follows: S1: Carding polyamide fiber and polyester fiber into a web, hot air bonding, hot rolling, cooling and forming, to obtain nonwoven fabric A; S2: treating the non-woven fabric A with plasma to obtain a primary non-woven fabric; S3: The casting solution is evenly coated on the surface of the non-woven fabric, and then immersed in an ethanol solution for 30-40 minutes and dried to obtain a hydrophilic non-woven fabric layer.

3. The processing technology of a high permeability composite nonwoven fabric according to claim 2, characterized in that: The casting solution comprises the following components: by weight, 5-8 parts of poly-L-lysine, 3-5 parts of glutaraldehyde, 10-12 parts of polyvinyl alcohol, 4-5 parts of acetic acid, and 1-2 parts of modified nano titanium oxide.

4. The processing technology of a high permeability composite nonwoven fabric according to claim 3 is characterized in that: The preparation process of the modified nano titanium oxide is: (1) Add nano titanium oxide and γ-aminopropyltriethoxysilane to a 10-20wt% ethanol aqueous solution in sequence, heat to 70-80°C, stir for 4-5h, wash, and dry to obtain amino nano titanium oxide; (2) Mix the amino-modified nano-titanium oxide, 2-2 (bromoacetyl) benzoic acid and dimethyl sulfoxide, stir for 30-40 minutes, then add dicyclohexylcarbodiimide and N-hydroxysuccinimide, continue stirring for 10-12 minutes, heat to 40-50°C, react for 5-8 hours, and obtain an intermediate; (3) The intermediate, tetrahydrofuran and triethylamine are mixed and stirred for 30-40 minutes. Under a protective atmosphere, N-butyl-m-toluidine is added dropwise. The temperature is raised to 60-70°C, and the reaction is carried out for 3-4 hours. The mixture is cooled to room temperature, washed and dried to obtain modified nano-titanium oxide.

5. The processing technology of a high permeability composite nonwoven fabric according to claim 4, characterized in that: The aminated nano titanium oxide comprises the following components: by weight, 20-25 parts of nano titanium oxide, 100-150 parts of ethanol aqueous solution, and 8-10 parts of γ-aminopropyltriethoxysilane; the intermediate comprises the following components: by weight, 30-35 parts of aminated nano titanium oxide, 10-12 parts of 2-2 (bromoacetyl) benzoic acid, 200-250 parts of dimethyl sulfoxide, 0.5-0.7 parts of dicyclohexylcarbodiimide, and 0.8-1 parts of N-hydroxysuccinimide; the modified nano titanium oxide comprises the following components: by weight, 10-15 parts of the intermediate, 80-100 parts of tetrahydrofuran, 3-4 parts of triethylamine, and 6-8 parts of N-butyl-meta-toluidine.

6. The processing technology of a high permeability composite nonwoven fabric according to claim 2, characterized in that: In the non-woven fabric A, the mass ratio of polyamide fiber to polyester fiber is (2-3):1; the temperature of the hot rolling process is 100-120°C; and the temperature of the cooling molding is 15-20°C.

7. The processing technology of a high permeability composite nonwoven fabric according to claim 2, characterized in that: The parameters of plasma treatment are: power 50-60 W, time 3-9 min, oxygen flux 50-80 mL / min.

8. The processing technology of a high permeability composite nonwoven fabric according to claim 1, characterized in that: The preparation process of the hydrophobic nonwoven fabric layer is as follows: polypropylene and modified nano titanium oxide are melt-extruded at 220-230° C., and after cooling, they are compressed and shaped at a temperature of 150-160° C. and a pressure of 4-5 Kg to obtain the hydrophobic nonwoven fabric layer.

9. The processing technology of a high permeability composite nonwoven fabric according to claim 8, characterized in that: The hydrophobic non-woven fabric layer comprises the following components: 100-120 parts of polypropylene and 5-6 parts of modified nano titanium oxide, by weight.

Citation Information

Patent Citations

  • Antibacterial spunlace non-woven fabric and preparation method thereof

    CN114148057A

  • Preparation method of hydrophilic polybutylene terephthalate non-woven fabric

    CN115772809A

  • Antibacterial modified polyethylene film as well as preparation method and application thereof

    CN117903520A

  • Cool-feeling breathable antibacterial fabric containing polyamide fibers and preparation method of cool-feeling breathable antibacterial fabric

    CN118205269A

Cited By

  • Polyester non-woven fabric and preparation method and application thereof

    CN120840226A